Lifespan Changes in Global and Selective Stopping and Performance Adjustments - Van De Laar, Maria C.; Van Den Wildenberg, Wery P.; van Boxtel, Geert; van der Molen, Maurits (Frontiers in Psychology, 2011)
This study examined stopping and performance adjustments in four age groups (M ages: 8, 12, 21, and 76 years). All participants performed on three tasks, a standard two-choice task and the same task in which stop-signal trials were inserted requiring either the suppression of the response activated by the choice stimulus (global stop task) or the suppression of the response when one stop signal was presented but not when the other stop signal occurred (selective stop task). The results showed that global stopping was faster than selective stopping in all age groups. Global stopping matured more rapidly than selective stopping. The developmental gain in stopping was considerably more pronounced compared to the loss observed during senescence. All age groups slowed the response on trials without a stop signal in the stop task compared to trials in the choice task, the elderly in particular. In addition, all age groups slowed on trials following stop-signal trials, except the elderly who did not slow following successful inhibits. By contrast, the slowing following failed inhibits was disproportionally larger in the elderly compared to young adults. Finally, sequential effects did not alter the pattern of performance adjustments. The results were interpreted in terms of developmental change in the balance between proactive and reactive control.